Effects of B-site Al doping on microstructure characteristics and hydrogen production performance of novel LaNixAl1-xO3-δ perovskite in methanol steam reforming. (1st April 2023) - Shen, Qiuwan; Shao, Zicheng; Li, Shian; Yang, Guogang; Sunden, Bengt
Abstract: A series of B-site aluminum doped LaNix Al1-x O3-δ (x = 0–1) perovskite samples were prepared by the sol-gel method and applied as catalysts for methanol steam reforming (MSR). The synthesized perovskite catalysts were characterized by SEM, XRD, SEM-EDS, XPS, TEM and BET. Results showed that LaNi0.4 Al0.6 O3-δ exhibited the highest methanol conversion and hydrogen production amount per unit time. However, the excessive aluminum content led to a decrease in H2 selectivity, and the high W/M promoted the reverse water-gas shift reaction (RWGS), which resulted in a decrease in CO selectivity and an increase in CO2 selectivity. The results of XRD, XPS and BET indicated that the LaNi0.4 Al0.6 O3-δ catalyst sample still exhibit a very typical perovskite structure after hydrogen reduction treatment. The results also indicated that there were active sites for MSR on the LaNi0.4 Al0.6 O3-δ sample that were not successfully reduced, but the specific surface area and porous characteristics of the catalyst were changed by H2 reduction treatment. The optimal reaction temperature, GHSV and W/M were determined to be 600 °C, 10, 520 h −1, 3:1, respectively. In addition, the LaNi0.4 Al0.6 O3-δ shows high catalytic activity within 20 h of stability test. The average methanol conversion and H2 selectivity during 20 h were 91% and 93% on average, respectively. Highlights: Experiments show LaNi0.4 Al0.6 O3-δ has highest methanol conversion and hydrogen production. LaNi0.4 Al0.6 O3-δ catalyst sample exhibits a very typical perovskite structure after hydrogen reduction. The amount of B-site aluminum doping in the perovskite has an impact on the catalytic performance. LaNi0.4 Al0.6 O3-δ is a potential catalyst for methanol steam reforming.